2015
DOI: 10.1016/j.sjpain.2015.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Oral oxycodone for pain after caesarean section: A randomized comparison with nurse-administered IV morphine in a pragmatic study

Abstract: Background and aims The present randomized open label parallel group study was conducted to evaluate if an oral oxycodone (OXY) regimen can be at least equally effective and as safe for postoperative analgesia after caesarean section (CS) as a standard of care program using nurse-administered intravenous morphine (IVM), followed by oral codeine. Methods Eighty women (40 + 40) were scheduled for elective CS under spinal anaesthesia. All patients received postoperative multimodal analgesic therapy, including ibu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
13

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 31 publications
0
19
0
13
Order By: Relevance
“…This has been documented for paracetamol and ibuprofen, and for paracetamol and diclofenac [16]. Niklasson and co-workers did administer paracetamol and ibuprofen to all of their post caesarean women, thus reducing the need for opioids [1].…”
Section: Exploit Non-opioid Analgesic Combinations Before Adding Opiomentioning
confidence: 95%
See 4 more Smart Citations
“…This has been documented for paracetamol and ibuprofen, and for paracetamol and diclofenac [16]. Niklasson and co-workers did administer paracetamol and ibuprofen to all of their post caesarean women, thus reducing the need for opioids [1].…”
Section: Exploit Non-opioid Analgesic Combinations Before Adding Opiomentioning
confidence: 95%
“…It is therefore particularly unfortunate to prescribe codeine-containing tablets for postoperative pain relief. Thus, Niklasson and co-workers found that oral oxycodone shortened the time to first defecation after CS compared with IV morphine and oral codeine [1].…”
Section: Opioid-induced Gastro-intestinal Dysfunction and Constipationmentioning
confidence: 99%
See 3 more Smart Citations